2011
DOI: 10.1094/ats-2011-1103-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Annual Bluegrass Control in Seedling Creeping Bentgrass with Bispyribac-sodium

Abstract: Golf course fairways may be renovated to replace different species or older cultivars of creeping bentgrass (Agrostis stolonifera L.) (CBG) with improved bentgrass cultivars. Older cultivars are often infested with annual bluegrass (Poa annua L.) (ABG), and a primary goal of the renovation is to remove ABG from the turf. A series of trials were conducted from 2004 to 2007 to determine optimum bispyribac‐sodium (BPS) application regimes to control ABG without excessive injury to establishing CBG. Bispyribac‐sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In CBG, bispyribac‐sodium is currently the industry standard for POST ABG control and has been thoroughly researched (McCullough and Hart, 2008, 2009; McCullough and Hart, 2010; McDonald et al, 2006). Multiple applications on 2‐ to 3‐week intervals are highly effective for ABG control (Branham and Sharp, 2011; McCullough and Hart, 2009, 2010). Lycan and Hart (2006) found that two applications made 3 weeks apart in August at the equivalent of 6.0 oz/ac 17.6WSP formulation are effective in controlling ABG.…”
Section: Useful Conversionsmentioning
confidence: 99%
“…In CBG, bispyribac‐sodium is currently the industry standard for POST ABG control and has been thoroughly researched (McCullough and Hart, 2008, 2009; McCullough and Hart, 2010; McDonald et al, 2006). Multiple applications on 2‐ to 3‐week intervals are highly effective for ABG control (Branham and Sharp, 2011; McCullough and Hart, 2009, 2010). Lycan and Hart (2006) found that two applications made 3 weeks apart in August at the equivalent of 6.0 oz/ac 17.6WSP formulation are effective in controlling ABG.…”
Section: Useful Conversionsmentioning
confidence: 99%